The role of integrated community case management projects in strengthening health systems: case study analysis in Ethiopia, Malawi and Mozambique - Story, William T; Pritchard, Susannah; Hejna, Emily; Olivas, Elijah; Sarriot, Eric (Health Policy and Planning, 2021)
Integrated community case management (iCCM) has now been implemented at scale globally. Literature to-date has focused primarily on the effectiveness of iCCM and the systems conditions required to sustain iCCM. In this study, we sought to explore opportunities taken and lost for strengthening health systems through successive iCCM programmes. We employed a systematic, embedded, multiple case study design for three countries—Ethiopia, Malawi and Mozambique—where Save the Children implemented iCCM programmes between 2009 and 2017. We used textual analysis to code 62 project documents on nine categories of functions of health systems using NVivo 11.0. The document review was supplemented by four key informant interviews. This study makes important contributions to the theoretical understanding of the role of projects in health systems strengthening by not only documenting evidence of systems strengthening in multi-year iCCM projects, but also emphasizing important deﬁciencies in systems strengthening efforts. Projects operated on a spectrum, ranging from gap-ﬁlling interventions, to support, to actual strengthening. While there were natural limits to the inﬂuence of a project on the health system, all successive projects found constructive opportunities to try to strengthen systems. Alignment with the Ministry of Health was not always static and simple, and ministries themselves have shown pluralism in their perspectives and orientations. We conclude that systems strengthening remains ‘everybody’s business’ and places demands for realism and transparency on government and the development architecture. While mid-size projects have limited decision space, there is value in better deﬁning where systems strengthening contributions can actually be made. Furthermore, systems strengthening is not solely about macro-level changes, as operational and efﬁciency gains at meso and micro levels can have value to the system. Claims of ‘systems strengthening’ are, however, bounded within the quality of evaluation and learning investments.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; health / saúde

Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Democracy Index 2020 In sickness and in health? - The Economist Intelligence Unit (The Economist, 2020)
The main focus of the report is the impact of the coronavirus (Covid-19) pandemic on democracy and freedom around the world. It looks at how the pandemic resulted in the withdrawal of civil liberties on a massive scale and fuelled an existing trend of intolerance and censorship of dissenting opinion (see page 14). The report also examines the state of US democracy after a tumultuous year dominated by the coronavirus pandemic, the Black Lives Matter movement and a hotly contested presidential election (see page 42). The results by region are analysed in greater detail in the section entitled “Democracy around the regions in 2020” (see page 26).
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; civil society / sociedade civil; health - COVID-19 / saúde – COVID-19

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Midwives’ perspectives on (dis)respectful intrapartum care during facility-based delivery in sub-Saharan Africa: a qualitative systematic review and meta-synthesis - Bradley, Susan; McCourt, Christine; Rayment, Juliet; Parmar, Divya (Reproductive Health, 2019)
Background: In the past decade, the negative impact of disrespectful maternity care on women’s utilisation and experiences of facility-based delivery has been well documented. Less is known about midwives’ perspectives on these labour ward dynamics. Yet efforts to provide care that satisfies women’s psycho-socio-cultural needs rest on midwives’ capacity and willingness to provide it. We performed a systematic review of the emerging literature documenting midwives’ perspectives to explore the broader drivers of (dis)respectful care during facility-based delivery in the sub-Saharan African context. Methods: Seven databases (CINAHL, PsychINFO, PsychArticles, Embase, Global Health, Maternity and Infant Care and PubMed) were systematically searched from 1990 to May 2018. Primary qualitative studies with a substantial focus on the interpersonal aspects of care were eligible if they captured midwives’ voices and perspectives. Study quality was independently assessed by two reviewers and PRISMA guidelines were followed. The results and findings from each study were synthesised using an existing conceptual framework of the drivers of disrespectful care. Results: Eleven papers from six countries were included and six main themes were identified. ‘Power and control’ and ‘Maintaining midwives’ status’ reflected midwives’ focus on the micro-level interactions of the mother-midwife dyad. Meso-level drivers of disrespectful care were: the constraints of the ‘Work environment and resources’; concerns about ‘Midwives’ position in the health systems hierarchy’; and the impact of ‘Midwives’ conceptualisations of respectful maternity care’. An emerging theme outlined the ‘Impact on midwives’ of (dis)respectful care. Conclusion: We used a theoretically informed conceptual framework to move beyond the micro-level and interrogate the social, cultural and historical factors that underpin (dis)respectful care. Controlling women was a key theme, echoing women’s experiences, but midwives paid less attention to the social inequalities that distress women. The synthesis highlighted midwives’ low status in the health system hierarchy, while organisational cultures of blame and a lack of consideration for them as professionals effectively constitute disrespect and abuse of these health workers. Broader, interdisciplinary perspectives on the wider drivers of midwives’ disrespectful attitudes and behaviours are crucial if efforts to improve the maternity care environment - for women and midwives - are to succeed.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Publisher: Centro Brasileiro de Análise e Planejamento
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

GFF Civil Society Engagement Strategy Addendum - Adolescent and Youth (AY) - Global Financing Facility (Global Financing Facility, 2018)
The Global Strategy for Women’s, Children’s and Adolescents’ Health 2016-30 highlights the importance of adolescent health and well-being as being essential to achieving the Sustainable Development Goals (SDG) by 2030. For adolescents to survive, thrive and transform their societies, the global community needs to invest in their health and well-being. Today’s adolescents are well-positioned to mobilize their peers, advocate for increased resources for sexual and reproductive health and rights, influence their governments to invest in addressing their needs, and demand accountability for commitments related to their health and development. The Global Financing Facility (GFF) Civil Society Engagement Strategy (CSES) and related implementation plan provide a clear framework for civil society organizations’ (CSOs) contribution to the improvement of health outcomes through coalition strengthening, meaningful participation in multi-stakeholder country platforms responsible for coordinating health plans and their implementation,1 and coordinated action in support of the achievement of national sexual, reproductive, maternal, newborn, child and adolescent health (SRMNCAH) goals. Youth and adolescent led organizations should use the CSES as the basis for their engagement in the GFF processes both at the global and national levels. This Adolescent and Youth (AY) addendum to the CSES outlines a deliberate approach to ensuring youth representation in the processes led by the GFF Civil Society Coordinating Group2 (CSCG) to ensure their meaningful and active participation in the design, implementation, monitoring and evaluation of their country investment case.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; development partners / parceiros de cooperação; health / saúde; youth / juventude

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

GFF Implementation Plan for the Gff Civil Society Engagment Strategy - Global Financing Facility (Global Financing Facility, 2017)
The implementation plan for the civil society engagement strategy (CSES) is developed to provide civil society organizations in countries (CSOs) with an operational framework to strengthen their engagement in the GFF process with a view to supporting the achievement of the objectives of the GFF and national investment cases. The plan reflects and builds on, and should be read in conjunction with the CSES. It is shaped and informed by GFF country implementation experiences to date, 12345 as well as the results of a targeted 2017 survey sent to CSOs working in GFF countries. The survey was geared towards understanding: 1) the civil society landscape in countries; 2) the level of knowledge of the GFF processes by CS; 3) priority actions CS can take to strengthen their engagement in the GFF processes and to support the achievement of the RMNCAH investment cases; and 4) what resources CS might need to better engage with national platforms and planning processes and to implement the identified supportive actions. The survey was sent to 18 organizations in 12 GFF countries and had a 61% response rate.
Sixth Invertors Group Meeting
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; health / saúde

Health provider responsiveness to social accountability initiatives in low- and middle-income countries: a realist review - Lodenstein, Elsbet; Dieleman, Marjolein; Gerretsen, Barend; Broerse, Jacqueline E W (Health Policy and Planning, 2017)
Social accountability in the health sector has been promoted as a strategy to improve the quality and performance of health providers in low- and middle-income countries. Whether improvements occur, however, depends on the willingness and ability of health providers to respond to societal pressure for better care. This article uses a realist approach to review cases of collective citizen action and advocacy with the aim to identify key mechanisms of provider responsiveness. Purposeful searches for cases were combined with a systematic search in four databases. To be included in the review, the initiatives needed to describe at least one outcome at the level of frontline service provision. Some 37 social accountability initiatives in 15 countries met these criteria. Using a realist approach, retroductive analysis and triangulation of methods and sources were performed to construct Context–Mechanism–Outcome configurations that explain potential pathways to provider responsiveness. The findings suggest that health provider receptivity to citizens’ demands for better health care is mediated by health providers’ perceptions of the legitimacy of citizen groups and by the extent to which citizen groups provide personal and professional support to health providers. Some citizen groups activated political or formal bureaucratic accountability channels but the effect on provider responsiveness of such strategies was more mixed. Favourable contexts for health provider responsiveness comprise socio-political contexts in which providers self-identify as activists, health system contexts in which health providers depend on citizens’ expertise and capacities, and health system contexts where providers have the self-perceived ability to change the system in which they operate. Rather than providing recipes for successful social accountability initiatives, the synthesis proposes a programme theory that can support reflections on the theories of change underpinning social accountability initiatives and interventions to improve the quality of primary health care in different settings.
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde

Mapping the use of research to support strategies tackling maternal and child health inequities: evidence from six countries in Africa and Latin America - Vargas, Emily; Becerril-Montekio, Victor; Gonzalez-Block, Miguel Ángel; Akweongo, Patricia; Hazel, Cynthia N. A.; Cuembelo, Maria de Fatima; Limbani, Felix; Bernardo, Wanderley; Muñoz, Fernando (Health Research Policy and Systems, 2016)
Background: Striving to foster collaboration among countries suffering from maternal and child health (MCH) inequities, the MASCOT project mapped and analyzed the use of research in strategies tackling them in 11 low- and middle-income countries. This article aims to present the way in which research influenced MCH policies and programs in six of these countries – three in Africa and three in Latin America. Methods: Qualitative research using a thematic synthesis narrative process was used to identify and describe who is producing what kind of research, how research is funded, how inequities are approached by research and policies, the countries’ research capacities, and the type of evidence base that MCH policies and programs use. Four tools were designed for these purposes: an online survey for researchers, a semi-structured interview with decision makers, and two content analysis guides: one for policy and programs documents and one for scientific articles. Results: Three modalities of research utilization were observed in the strategies tackling MCH inequities in the six included countries – instrumental, conceptual and symbolic. Instrumental utilization directly relates the formulation and contents of the strategies with research results, and is the least used within the analyzed policies and programs. Even though research is considered as an important input to support decision making and most of the analyzed countries count five or six relevant MCH research initiatives, in most cases, the actual impact of research is not clearly identifiable. Conclusions: While MCH research is increasing in low- and middle-income countries, the impact of its outcomes on policy formulation is low. We did not identify a direct relationship between the nature of the financial support organizations and the kind of evidence utilization within the policy process. There is still a visible gap between researchers and policymakers regarding their different intentions to link evidence and decision making processes.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Disrespect and Abuse During Childbirth in Tanzania: Are Women Living With HIV More Vulnerable? - Sando, David; Kendall, Tamil; Lyatuu, Goodluck; Ratcliffe, Hannah; McDonald, Kathleen; Mwanyika-Sando, Mary; Emil, Faida; Chalamilla, Guerino; Langer, Ana (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2014)
Introduction: HIV-related stigma and discrimination and disrespect and abuse during childbirth are barriers to use of essential maternal and HIV health services. Greater understanding of the relationship between HIV status and disrespect and abuse during childbirth is required to design interventions to promote women's rights and to increase uptake of and retention in health services; however, few comparative studies of women living with HIV (WLWH) and HIV-negative women exist. Methods: Mixed methods included interviews with postpartum women (n = 2000), direct observation during childbirth (n = 208), structured questionnaires (n = 50), and in-depth interviews (n = 18) with health care providers. Bivariate and multivariate regressions analyzed associations between HIV status and disrespect and abuse, whereas questionnaires and in-depth interviews provided insight into how provider attitudes and workplace culture influence practice. Results: Of the WLWH and HIV-negative women, 12.2% and 15.0% reported experiencing disrespect and abuse during childbirth (P = 0.37), respectively. In adjusted analyses, no significant differences between WLWH and HIV-negative women's experiences of different types of disrespect and abuse were identified, with the exception of WLWH having greater odds of reporting non-consented care (P = 0.03). None of the WLWH reported violations of HIV confidentiality or attributed disrespect and abuse to their HIV status. Provider interviews indicated that training and supervision focused on prevention of vertical HIV transmission had contributed to changing the institutional culture and reducing HIV-related violations. Conclusions: In general, WLWH were not more likely to report disrespect and abuse during childbirth than HIV-negative women. However, the high overall prevalence of disrespect and abuse measured indicates a serious problem. Similar institutional priority as has been given to training and supervision to reduce HIV-related discrimination during childbirth should be focused on ensuring respectful maternity care for all women.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

The group effect: Social cohesion and health outcomes - Bruhn, John (Springer New York, NY, 2009)
Sociologists and anthropologists have had a long interest in studying the ways in which cultures shaped different patterns of health, disease, and mortality. Social scientists have documented low rates of chronic disease and disability in non-Western societies and have suggested that social stability, cultural homogeneity and social cohesion may play a part in explaining these low rates. On the other hand, in studies of Western societies, social scientists have found that disease and mortality assume different patterns among various ethnic, cultural and social-economic groups. The role of stress, social change and a low degree of cohesion have been suggested, along with other factors as contributing to the variable rates among different social groups. Social cohesion has been implicated in the cause and recovery from both physical and psychological illnesses. Although there has been a large amount of work established the beneficial effects of cohesion on health and well-being, relatively little work has focused on HOW increased social cohesion sustains or improves health. This work is based on the premise that there are risk factors, including social cohesion that regulate health and disease in groups. One of the challenges is how to measure social cohesion - it can be readily observed and experienced but difficult to quantify. A better understanding of how social cohesion works will be valuable to improving group-level interventions. © Springer Science+Business Media, LLC 2009. All rights reserved.
Journal Abbreviation: tThe Group Effect: Social Cohesion and Health Outcomes Pages: 171 Publication Title: tThe Group Effect: Social Cohesion and Health Outcomes
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; health / saúde

Collaboration and competition in a children's health initiative coalition: A network analysis - Valente, Thomas W.; Coronges, Kathryn A.; Stevens, Gregory D.; Cousineau, Michael R. (Evaluation and Program Planning, 2008)
Activating communities to achieve public health change and initiate policy reform usually requires collective action from many entities. This case study analyzes inter-organizational networks among members of a coalition created to expand health insurance coverage to uninsured children in a large metropolitan area. Six networks were measured: collaboration, competition, formal agreements, receive funding from, send funding to, and greater communication. The response rate was 65.8% (50 of the 76 active members). Positive network questions such as “who do you collaborate with” elicited many network choices whereas negative ones such as “who do you compete with” elicited few. The collaboration network had a core–periphery structure and analysis showed that a large network can be reduced to a small set of core organizations one-sixth the size of the whole. Centrality (out- and in-degree) was associated with perceived organizational function and perceived barriers to success. For example, organizations that received many choices as collaboration partners were more likely to perceive the coalition functioned well than those who received few choices. The study suggests that perceptions of organizational performance are associated with position in the network, central members are more likely to perceive the organization performs well than those on the periphery.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; M - methodology / metodologia; access to services / acesso a serviços; collaboration / colaboração; health - maternal and child / saúde - materno-infantil; health / saúde

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde

Health providers’ opinions on provider–client relations: results of a multi-country study to test Health Workers for Change - Fonn, S; Mtonga, AS; Nkoloma, HC; Bantebya Kyomuhendo, G; Dasilva, L; Kazilimani, E; Davis, S; Dia, R (Health Policy and Planning, 2001)
A multi-centre study in four African countries was undertaken to test the acceptability and effectiveness of Health Workers for Change, a methodology to explore provider–client relations within a gender-sensitive context. This intervention addresses the interpersonal component of quality of care. The methodology, consisting of six workshops, was implemented by research teams in Zambia, Senegal, Mozambique and Uganda. It was found to be acceptable within in a range of cultural and primary health care settings. The workshops allowed difficult issues such as prejudice and bribery to be discussed openly, fostered problem solving and the development of practical plans to address problems that could strengthen district health systems.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

Introduction: Accountability through Participation: Developing Workable Partnership Models in the Health Sector - Cornwall, Andrea; Lucas, Henry; Pasteur, Kath (IDS Bulletin, 2000)
The IDS Participation and Health and Social Change Groups convened a workshop in October 1999 to share experience with the use of participatory approaches in enhancing accountability in the health sector, and to explore some of these challenges. The articles in this bulletin reflect some of the richness of experience on the ground in building effective participation, as well as some of the many issues that arise in moving towards more active citizen engagement with service provision. They bring experience from current and ongoing work to reflect on the links between participation, accountability and improvements in health. The workshop explicitly aimed to reflect on experiences that were moderately successful, in order to identify potential elements that contribute to and impede the success of efforts to build accountability through participation. It is important to emphasise that understanding of the complexities of this approach is at a very early stage. The design of interventions is complex and often highly contextdependent. Rather than attempt to establish any blueprint for future activities, the workshop sought to explore the issues and attempt to advance the debate. In this introduction we draw out some of the principal themes emerging from the articles included here, and from workshop discussions.
Accepted: 2016-02-01T14:49:31Z Publisher: Institute of Development Studies
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health / saúde